Evaluation of leaching potential of tebuthiuron using bioindicator plants - Silva Junior, Antonio Carlos Da (2018)
ABSTRACT: The last destination of most herbicides used in agricultural systems is the soil. This is a dynamic interaction; herbicides can remain in the soil solution or be carried through the soil profile, reaching the water table. The objective of this work was to evaluate the leaching potential of the tebuthiuron herbicide using bioindicator plants grown in an Oxisol of sandy loam texture and in an Entisol of clay texture, after the occurrence of natural rainfall events. A complete randomized experimental design was used, in a 3×8 factorial arrangement, with four replications. The treatments consisted of three accumulated natural rainfall depths (30-40, 60-80, and 100-120 mm) and eight soil profile layers (0-3, 3-6, 6-9, 9-12, 12-15, 15-20, 20-25, and 25-30 cm). Soil samples were collected after the tebuthiuron herbicide application - 750 for clayey soil, and 600 g ha-1 for the sandy loam soil -and the rainfall events. PVC pipes with length of 30 cm and diameter of 15 cm were introduced into the soil profile for sampling. The pipes with soil columns were carefully removed by digging around them, to maintain the soil original integrity during collection and, subsequently, cut longitudinally for sowing the bioindicator species - cucumber (Cucumis sativus L.), and lettuce (Lactuca sativa L.). Then, the phytotoxicity in the bioindicator plants grown in these soils were evaluated at 5, 7, 10, and 12 days after sowing, using a grading scale of 0 to 100%. The mobility of the tebuthiuron herbicide was low in both soils, regardless of the rainfall depth, and the cucumber was the most suitable plant species to use as a bioindicator.